1979
DOI: 10.1161/01.res.45.1.48
|View full text |Cite
|
Sign up to set email alerts
|

Central neural mechanisms of the cerebral ischemic response. Characterization, effect of brainstem and cranial nerve transections, and simulation by electrical stimulation of restricted regions of medulla oblongata in rabbit.

Abstract: THE CEREBRAL ischemic response consists of an elevation of arterial pressure

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…In contrast with the rapid cessation of the cortical electrical activity by ischemia, the vasomotor center in the ventrolateral medulla as well as the cardioinhibitory center, i.e., nucleus ambiguus or dorsal motor nucleus, are excited by ischemia to produce the characteristic cerebral ischemic response (22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the rapid cessation of the cortical electrical activity by ischemia, the vasomotor center in the ventrolateral medulla as well as the cardioinhibitory center, i.e., nucleus ambiguus or dorsal motor nucleus, are excited by ischemia to produce the characteristic cerebral ischemic response (22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral hypoxia or ischemia elicits a rapid, patterned, autonomic response, which originates in the lower brainstem (Dampney et al, 1979;Guyenet and Brown, 1986) and includes sympathetic excitation, visceral and muscular vasoconstriction, bradycardia, and expiratory apnea (Dampney et al, 1979;Dampney and Moon, 1980;Guyenet and Brown, 1986;. In addition, there is a widespread increase in regional cerebral blood flow (rCBF) without change in a cerebral metabolism [as evaluated by regional cerebral glucose utilization (rCGU)] and synchronization of the EEG (Underwood et al, 1992(Underwood et al, , 1994Golanov and Reis, 1996;Golanov et al, 2000b;).…”
mentioning
confidence: 99%
“…13 25 -28 produce increases in arterial blood pressure and coronary vasoconstriction, which is often marked. In the present study, coronary vasoconstriction was observed during cerebral ischemia, but the neurogenic component of this vasoconstriction resulted from concurrent changes in baroreceptor activity and was not an independent effect of cerebral ischemia.…”
Section: Physiological Importancementioning
confidence: 99%